Reformasi Birokrasi Kabupaten Kerinci: Strategi Peningkatan Efisiensi dan Kualitas Pelayanan Publik - Awal Khairi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Abstract. Bureaucratic reform in Indonesia is an important agenda in improving government performance, especially in public services. Kerinci Regency, Jambi Province, faces various challenges in carrying out bureaucratic reforms, such as low capacity of civil servants, limited infrastructure, and resistance to change. Weber's bureaucratic theory, New Public Management (NPM), and the concepts of efficiency, effectiveness, and transparency are the theoretical framework for understanding the importance of bureaucratic reform. This study uses a qualitative descriptive approach with in-depth interview methods and direct observation. The results of the study show that Kerinci Regency has implemented bureaucratic reform policies, such as simplifying service procedures and using information technology. However, various obstacles such as the lack of ASN capacity and limited infrastructure hinder the implementation of reforms as a whole. The positive impacts identified are increased community satisfaction, transparency, and accountability of local governments. This research recommends increasing the capacity of civil servants, expanding the implementation of e-government, and strengthening service infrastructure to support more effective and sustainable bureaucratic reform. Thus, bureaucratic reform in Kerinci Regency can encourage public services that are more efficient, transparent, and responsive to the needs of the community.